Pelatihan Auto Level untuk Survei Lokasi pada SMKN 4 SPP Singkawang: Auto Level Training for Location Survey at SMKN 4 SPP Singkawang - Anggraini, Irene; Hafiyyan, Qalbi; Rabihati, Etty; Ryanti, Eva; Muhtadi, Ahmad; Purnama, Ikhwan Arief; Setiawan, Randy; Rizal, Rizal; Sasongko, Hartanto Wahyu; Perangin Angin, Imanuel Kemenangenta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
SMKN 4 SPP Singkawang is one of the vocational schools that provides education with a focus on agriculture and agribusiness. The purpose of providing education at this school is to produce graduates who are skilled in agriculture. One of the important skills to have in agriculture is topographic surveying. For this reason, students at school are expected to have these skills. These skills can later be used to support various activities in agriculture, such as irrigation planning and determining plant types based on topographic conditions. Topographic surveys can be carried out effectively and efficiently using optical tools such as auto levels. Based on this, Community Service (PKM) activities in the form of auto level training were carried out by students at SMKN 4 SPP Singkawang. The purpose of this training is for students to be able to use auto levels in mapping land contours for agricultural and agribusiness purposes. The training began by providing an explanation of the optical tools that would be used for the survey. The next stage is for students to practice using the optical tools accompanied by the Community Service (PKM) team. The result of this training is that students are able to understand and practice measuring land contours using auto levels. Finally, this training is expected to improve the skills of students of SMKN 4 SPP Singkawang, which will later be able to support various activities in the fields of agriculture and agribusiness, such as irrigation planning, determining plant types, and so on.